Partial characterisation of ATP-binding cassette encoding genes in Cryptosporidium parvum - Chan, Li Li; Fong, Mun Yik (Penerbit Universiti Sains Malaysia, 2004)
Cryptosporidium parvum is an intestinal parasitic protozoa which causes self-limited diarrhoea in immunocompetent individuals and devastating and fulminant diarrhoea in immunocompromised patients (Griffiths, 1998).